HOW PARTICIPATION SHAPES LOCAL DEVELOPMENT - Muhadjir Darwin (Populasi, 2016)
This article elaborates citizens’ participation in shaping local development in the Indonesian context. The main question is how to make local development more participatory as a guarantee that citizens’ rights are fully realized. In that respects, social accountability is a key that should be improved from supply and demand sides simultaneously. From the supply side, there is a need to reform local governance, in order to improve the quality of local regulations, local planning, local budgeting, and local public service provision. While from the demand side, there is a need to empower local citizens so that they are engaged in five forms or local development efforts: local regulation formulation, local development planning, local budgeting, community driven development, and public service provision.